Is Classical Arabic a Dead Variety? - Ben-Naji, Awatef A. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This paper presents a literature based review of the current status of Classical Arabic. The death or vitality of Classical Arabic is a controversial topic which raised the interests of many scholars and researches for a long period of time. It shall be argued in this review that Classical Arabic is a living variety and can never vanish for a number of reasons. The researcher begins by revisiting the literature of Classical Arabic. Then, different views and debates concerning the sociolinguistic situation of Classical Arabic are deeply discussed and investigated. Finally, evidences are provided that support the researcher's overview of the liveliness of Classical Arabic.
Keywords: Holy Qur’ān; Classical Arabic (CA); Colloquial dialects; Diglossia; Arab nationalism